PEMILIHAN BAHASA ETNIK BUGIS DALAM RANAH KELUARGA BERDASARKAN HUBUNGAN PERAN DAN KATEGORI UMUR DI KABUPATEN DONGGALA - NFN Tamrin (Balai Bahasa Sulawesi Tengah, 2016)
A speaker in a multilanguage must have a language choice to define a language whichto be used in communication. Indonesian people consists of various cultures, races, andethnics, and also variety of languages which they used to communicated between theirfamilies and socities. This research wants to find out the language choice of Bugineseethnic in the family domain based on roles relation and age category in DonggalaRegency. This research aims to (1) described the patterns of language choice of theBuginese ethnic in the family domain based on roles relation and age category inDonggala Regency; (2) to analyzed the based factors of language choice of theBuginese ethnic in the family domain based on roles relation and age category inDonggala Regency. This research used a sociolinguistics approach method byquestionnaire, interview, observe, and record. The data analyzed based on thepercentage of language choice of the Buginese ethnic in family domain. The resultsshows that Buginese ethnic in Donggala Regency, 83,7% used Buginese as a meduim ofcommunication in family domain, 7,7% used Bahasa Indonesia, and 8,3% used both ofBuginese and Bahasa Indonesia, and only 0,3 % used mother tongue (DampalLanguage).